2011
DOI: 10.1117/1.3528043
|View full text |Cite
|
Sign up to set email alerts
|

Optimized solution-processed merocyanine:PCBM organic bulk heterojunction solar cell

Abstract: Abstract. We present the in-depth investigation of solution-processed bulk-heterojunction solar cells based on the merocyanine dye MD304 as a donor in combination with the soluble fullerene derivative [6,6]-phenyl-C 61 -butyric acid methyl ester (PCBM) as acceptor. The optimized MD304:PCBM devices exhibit an external quantum efficiency of ca. 50%, and a power conversion efficiency of up to 2.1% under standard illumination and 2.7% under reduced illumination intensities. Because of the strongly dipolar characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The as grown MHJ showed an increased J SC but a lower FF in comparison to those of the reference BHJ solar cell. In our previous studies on BHJ solar cells, postproduction thermal annealing had no influence on cell performance . However, the investigation of OTFTs with dye 4 described above and previous studies of annealing on the performance of PHJ devices suggested that postproduction annealing should be applied to the MHJ device in order to recover the FF.…”
Section: Resultsmentioning
confidence: 89%
“…The as grown MHJ showed an increased J SC but a lower FF in comparison to those of the reference BHJ solar cell. In our previous studies on BHJ solar cells, postproduction thermal annealing had no influence on cell performance . However, the investigation of OTFTs with dye 4 described above and previous studies of annealing on the performance of PHJ devices suggested that postproduction annealing should be applied to the MHJ device in order to recover the FF.…”
Section: Resultsmentioning
confidence: 89%
“…An increasing number of donor candidate molecules for organic photovoltaics (OPVs) with alternating electron donor (D) and acceptor (A) subunits have been reported in recent years. Among simple dyes, dipolar merocyanines (MCs) are an interesting and versatile class of functional materials. , MC donor–acceptor (D–A) groups can be easily changed to tune their absorption from the blue to IR spectral region, with ground-state dipole moments ranging from 3 to 15 D. MCs have been applied as active component in bulk heterojunction (BHJ) OPV devices. A previous study by Kronenberg et al showed that BHJ OPVs composed of indoline-based MC donors and [6,6]-phenyl-C 61 -butyric acid methyl ester (PCBM) or C 60 acceptors manifest in large open-circuit voltages ( V OC ) and short-circuit currents ( J SC ) of 0.9, 0.76 V and 5.3, 6.3 mA/cm 2 , respectively. However, poor charge transport gave rise to low fill factors (FFs) (∼30%) resulting in power conversion efficiencies (PCEs) of 1.5 and 1.7% .…”
Section: Introductionmentioning
confidence: 99%